Developing Board Game Media Based on Egrang Batok to Support Aksara Sunda Learning in PGSD - Widiastuti, Hesti; Cep; Sinta; Anggy; Yulistina (IJORER : International Journal of Recent Educational Research, 2025)
The objective of this study is to design and develop learning media in the form of a game board inspired by the traditional egrang batok game. The utilization of Egrang Batok media has been the subject of prior research; however, no studies have been conducted on Sundanese language content. The objective of this media is to facilitate the acquisition of Sundanese script by PGSD students. Following the observation that students encountered difficulties in comprehending and acquiring proficiency in Sundanese script through the utilization of visual media exclusively, the author endeavored to conceptualize a board game employing the principles of batok egrang as a medium for Sundanese script instruction. The present study employed the ADDIE development model, which comprises five stages: The following sequence of steps is imperative: analysis, design, development, implementation, and evaluation. The findings of the research suggest that: The batok engrang board game medium has been determined to have a high level of validity, with an average score of 0.90 for content, 0.80 for media, and 0.8 for language, classified as sufficiently high. In terms of practicality, questionnaire results from teachers and students indicate that this medium is highly practical to use, with an average score of 95%. On the whole, the Egrang Batok-based board game is regarded as suitable and effective for use in learning activities at PGSD.